Methodological aspects in the study of species richness, diversity and homotony of grass cover - F. Klimeš; L. Kolář; J. Květ; W. Opitz Von Boberfeld; H. Laser (Plant, Soil and Environment, 2007)
This work proposes a new method for the assessment of species richness, diversity, and homotony in related vegetation relevés of grass swards. Hypothetical vegetation relevés with identical species number but differing constancy were generated to compare the techniques describing the species variety and diversity. By calculating these theoretical values in combination with data from real swards of Alopecuretum meadows, it has been shown that the determination of the constancy of particular species is essential for the evaluation of species diversity of grass swards. The relationship between the share of different combinations of vegetation relevés in the whole sample and corresponding total number of plant species were expressed by generating regression equations and the mid values of these curves were worked out and evaluated for individual sets of relevés; it was then possible to create homotony/heterotony indices for these sets. The indices of heterotony can be used, e.g., for expressing biotope diversity within a set of vegetation relevés from different stands.